2003
DOI: 10.1246/cl.2003.358
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Visible Light-Activated Titania Photocatalyst by Mechanochemical Method

Abstract: Nitrogen-doped yellowish rutile titania prepared by high energy ball milling of P-25 titania - 5% HMT (Hexamethylenetetramine, C6H12N4) mixed powders followed by calcination in air at 400 °C possessed two absorption edges around 400 and 540 nm and showed excellent photocatalytic ability for nitrogen monoxide oxidization under irradiation of the visible light of wavelength >510 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
94
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(100 citation statements)
references
References 10 publications
4
94
0
2
Order By: Relevance
“…However, it is active only in the ultraviolet (UV) region because of its wide band gap (3.0-3.2 eV), which accounts for less than 5% of solar energy [3]. Recent studies have revealed that the shortcoming of TiO 2 can be overcome by doping the nonmetal elements such as nitrogen [4][5][6], boron [7], sulfur [8], carbon [9], etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is active only in the ultraviolet (UV) region because of its wide band gap (3.0-3.2 eV), which accounts for less than 5% of solar energy [3]. Recent studies have revealed that the shortcoming of TiO 2 can be overcome by doping the nonmetal elements such as nitrogen [4][5][6], boron [7], sulfur [8], carbon [9], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Since urea has been reported as a N source for mechanical N-doping [15], in the previous paper we reported briefly the application of guanidine hydrochloride as a nitrogen source for N-doping [16]. In the present work, we tried several nitrogen-source compounds for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing a novel method that provides TiO 2 photocatalyst with sufficient photosensitivity in the visible light region and enhances charge separation in the electron-transfer process has been one of major research efforts in recent years [6][7][8][9]. For this purpose, many methods were investigated including doping of transition metals [10,11], nitrogen (N) [12][13][14][15], sulphur (S) [16][17][18] and fluorine [19][20][21][22] to improve the photocatalytic activity of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Doping of single elements, such as N [12][13][14][15] and S [16][17][18] was investigated to improve photocatalytic efficiency of TiO 2 due to the resulted oxynitrides and oxysulfides absorbing visible light to some extent. However, few reports were presented to dope bi-or multi-elements in TiO 2 catalysts.…”
Section: Introductionmentioning
confidence: 99%